Iranian-Iraqi conflict - Pesantes, Carlos (Revista Universidad de Guayaquil, 1987)
The Arab East has been the scene, since 1980, of the most disturbing war conflict in the world, contemporary for both capitalism and socialism. The Arab-Persian Gulf had been guaranteeing the normal flow of crude oil to the industrialized world until in February 1979, a religious-political-nationalist insurrection installed AYATOLLAH RUHO-LLAN KOMEINI in the Iranian government, throwing away a 2,500-year-old monarchy. From now on the peace of this stretch of Asian soil will begin to destabilize with the intransigence of the Ayatollah and his millions of Shiites threatening the "export of the revolution and the resurgence of Islamization."